Carfilzomib, lenalidomide, and dexamethasone in relapsed refractory multiple myeloma: a prospective real-life experience of the Regional Tuscan Myeloma Network - Antonioli, Elisabetta; Pilerci, Sofia; Attucci, Irene; Buda, Gabriele; Gozzetti, Alessandro; Candi, Veronica; Simonetti, Federico; Giudice, Maria Livia Del; Ciofini, Sara; Staderini, Michela; Grammatico, Sara; Buzzichelli, Alessandra; et al. (Frontiers in Oncology, 2023)
Carfilzomib, a potent, irreversible, selective proteasome inhibitor has demonstrated consistent results in relapsed/refractory myeloma (RRMM) combined with lenalidomide and dexamethasone (KRd). No prospective studies are yet available that analysed the efficacy of KRD combination. Herein we report a multicentre prospective observational study on 85 patients, who were treated with KRd combination as second or third line of treatment, according to standard practice. Median age was 61 years old; high-risk cytogenetic was found in 26% and renal impairment (eGFR < 60 ml/min) in 17%. After a median follow up of 40 months, patients had received a median number of 16 cycles of KRd, with median duration of treatment (DoT) of 18 months (range: 16.1–19.2 months). The overall response rate was 95%, with high-quality response (≥ very good partial remission [VGPR]) in 57% of the patients. The median PFS was 36 months (range: 29.1–43.2 months). Achievement of at least VGPR and a previous ASCT were associated with longer PFS. The median OS was NR; 5-year OS rate was 73%. Nineteen patients performed KRd treatment as a bridge to autologous transplantation, obtaining a post-transplant MRD negativity in 65% of cases. The most common adverse events were haematological, followed by infection and cardiovascular events, rarely G3 or higher, with a discontinuation rate for toxicities of 6%. Our data confirmed the feasibility and safety of the KRD regimen in real life.